Chinese Medical Teams in the DRC: A Comparative Case Study - Xiaoxiao Jiang Kwete (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This paper by Xiaoxiao Jiang Kwete analyzes China's program of sending a Chinese Medical Team (CMT) to an African country, in this case the Democratic Republic of Congo (DRC). The CMT in the DRC, from HeBei Province, started its 15th deployment in May 2012, for a two-year mission in the Chinese-Congolese Friendship Hospital in Kinshasa. This brief focuses on the challenges the CMT faced in the DRC, compares it to Médecins Sans Frontières's operations in the DRC, and proposes recommendations for improvements in the future.
Keywords: 330